Efforts to Empower Women Heads of Households in The Economic Sector in Depok City - Imam Budi Hartono; Prijono Tjiptoherijanto; Chotib Chotib (Universitas Sultan Ageng Tirtayasa, 2024)
Empowerment of Women-Headed Households (PEKKA) is a community to improve gender equality, welfare, and the economy. The purpose of the study is to improve the economic empowerment of communities and vulnerable groups in PEKKA, with the aim of increasing entrepreneurial growth. The author conducted a survey of 110 randomly selected people and in-depth interviews with 5 PEKKA members. The results of the in-depth interviews were analyzed with Dedoose software. Based on the findings in the field and the results of the interviews, the variables that must be addressed by the Depok City Government to support the success of PEKKA members in running their businesses are economic independence, gender equality, availability of access to product marketing, bazaars at various levels from urban village to national level, availability of access to capital, and CSR capital assistance from established local entrepreneurs.